Chinese Vaccine Diplomacy in the Eastern Mediterranean: Continuities and Rupture in Beijing’s Soft Power Prospects - ÜNGÖR SUNAR, ÇAĞDAŞ (My University, 2023)
© The Author(s) 2023.This article examines China’s vaccine drive in Eastern Mediterranean countries of Türkiye, Egypt, Syria, Lebanon, and the Palestinian territories during 2020–2021 from a soft power angle. 1 Although Chinese COVID-19 era health diplomacy is presented as a major breakthrough in the West, this study argues that continuities are more visible in the Eastern Mediterranean context with regard to China’s discourse and diplomatic practices. Beijing invested in the existing notions of propaganda, such as solidarity with developing countries, anti-Americanism, and economic partnership. In assessing the impact of Chinese vaccine diplomacy in the Eastern Mediterranean, the study investigates major diplomatic events and concludes that China could not improve its image in Türkiye in the aftermath of the COVID-19 pandemic.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; İktisat; Bilim, Teknoloji ve Toplum; Social Sciences and Humanities; Sociology; General Sociology and Methodology; Economics; Science, Technology and Society; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Ekonomi ve İş; Sosyal Bilimler Genel; KÜLTÜREL ÇALIŞMALAR; EKONOMİ; SOSYOLOJİ; SİYASET BİLİMİ; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; ECONOMICS & BUSINESS; SOCIAL SCIENCES, GENERAL; CULTURAL STUDIES; ECONOMICS; SOCIOLOGY; POLITICAL SCIENCE; Kültürel çalışmalar; Sosyal Bilimler ve Beşeri Bilimler; Sosyoloji ve Siyaset Bilimi; Ekonomi ve Ekonometri; Siyasi bilimler ve Uluslararası İlişkiler; Cultural Studies; Social Sciences & Humanities; Sociology and Political Science; Economics and Econometrics; Political Science and International Relations; China; Eastern Mediterranean; Egypt; Lebanon; Palestinian territories; soft power; Syria; Türkiye; vaccine diplomacy